Proteome and phosphoproteome of Africanized and European honeybee venoms - Resende, Virgínia Maria Ferreira; Vasilj, Andrej; Santos, Keity Souza; Palma, Mario Sergio [UNESP]; Shevchenko, Andrej (Wiley, 2013)
Honey bee venom toxins trigger immunological, physiological, and neurological responses within victims. The high occurrence of bee attacks involving potentially fatal toxic and allergic reactions in humans and the prospect of developing novel pharmaceuticals make honey bee venom an attractive target for proteomic studies. Using label-free quantification, we compared the proteome and phosphoproteome of the venom of Africanized honeybees with that of two European subspecies, namely Apis mellifera ligustica and A. m. carnica. From the total of 51 proteins, 42 were common to all three subspecies. Remarkably, the toxins melittin and icarapin were phosphorylated. In all venoms, icarapin was phosphorylated at the 205Ser residue, which is located in close proximity to its known antigenic site. Melittin, the major toxin of honeybee venoms, was phosphorylated in all venoms at the 10Thr and 18Ser residues. 18Ser phosphorylated melittin-the major of its two phosphorylated forms-was less toxic compared to the native peptide. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Animal proteomics; Apis mellifera; Honeybee venom; LC-MS/MS; Melittin; Phosphorylation; amino acid; bee venom; icarapin; melittin; phosphoprotein; phosphoproteome; proteome; serine; unclassified drug; Africa; amino acid substitution; Europe; honeybee; insect; liquid chromatography; mass spectrometry; nonhuman; peptide analysis; priority journal; protein analysis; protein database; protein phosphorylation; proteomics; quantitative analysis; species comparison; toxin analysis